Social Control Movement as a Corruption Eradication Instrument in Indonesia - Satria Unggul Wicaksana Prakasa (Universitas Slamet Riyadi, 2020)
Corruption in Indonesia is an endemic problem. It has been hampering the development, disconnecting hopes of fulfilling the fundamental constitutional rights of citizens, creating a repressive government, and harming the country's finances and economy. This research tries to find the right movement pattern of social control, such as whether in efforts to prevent and eradicate corruption in Indonesia. The conclusion from this legal research is that the movement of social control as an instrument to eradicate corruption in Indonesia has been described both in the aspect of Judicial review, Class Action and Citizen Law Suit (CLS), Court Monitoring, and the Whistleblower System (WbS), as well as non-legal movements (public hearing & advocacy, mass actions) that are not facultative, meaning that all efforts can be undertaken by civil society by being bridged by NGOs and the campus in the corruption eradication agenda in Indonesia Going forward, the challenge of eradicating corruption in Indonesia is increasingly tricky and steep, it requires commitment from all parties to strengthen commitments to eradicate corruption, create integrity zones, and more importantly enhance the KPK as an independent anti-corruption institution, as mandated by UNCAC to maintain the independence of anti-corruption in Indonesia.Keywords:Social-Control Movement, Law Enforcement, Anti-Corruption